Ecological Profile of the Flea Beetle Genus Calotheca Heyden in South Africa (Chrysomelidae, Galerucinae, Alticini) - Maurizio Biondi; Mattia Iannella; Paola D’Alessandro (Insects)
In this work, the 25 species of the flea beetle genus Calotheca Heyden recorded for South Africa are considered. Starting from the updated species distribution and the topographic, temperature, and precipitation variables, as well as the vegetation types in the occurrence sites, through an analysis of ecological niche modelling, a possible ecological profile is provided, both for each species and the entire genus, highlighting some of the factors that drive their occurrence and distribution patterns. Along with the vegetation type, some climatic variables were found to be particularly influential, such as the mean temperature of both the wettest and driest quarters and also the mean precipitation of the wettest period. Finally, comparing the distribution of the areas of highest suitability returned by the model obtained for Calotheca, they largely overlap with the highest-density areas of Searsia, genus of Anacardiaceae, including the main host plants for these flea beetles.